2016
DOI: 10.3171/2015.5.jns15327
|View full text |Cite
|
Sign up to set email alerts
|

Age-related outcomes following intracranial aneurysm treatment with the Pipeline Embolization Device: a subgroup analysis of the IntrePED registry

Abstract: A dvAncing age is a well-known risk factor for periprocedural morbidity and mortality after both surgery and coil embolization of intracranial aneurysms. 4,11,13 Flow diversion is a more recently developed endovascular technique, and several single-center and multicenter series have reported encouraging early results, especially in the treatment of complex proximal internal carotid artery (ICA) aneurysms.1-3 However, given the relatively small size of these series, the effect of age on periprocedural complicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 13 publications
1
15
1
Order By: Relevance
“…Increased age was also associated with higher odds of neurologic morbidity. 20 Our data found a nonsignificant trend toward increased complications in patients older than 70 years of age.…”
Section: Age-related Variation In Occlusion Ratescontrasting
confidence: 62%
See 1 more Smart Citation
“…Increased age was also associated with higher odds of neurologic morbidity. 20 Our data found a nonsignificant trend toward increased complications in patients older than 70 years of age.…”
Section: Age-related Variation In Occlusion Ratescontrasting
confidence: 62%
“…As one might expect, as patients age, the risk of complications appears to increase. Brinjikji et al, 20 in a large multicenter study on complications associated with PED placement, found that complication rates rise as the patient age increases. Patients older than 70 years of age had significantly higher rates of neurologic mortality.…”
Section: Age-related Variation In Occlusion Ratesmentioning
confidence: 99%
“…Operation possesses a significant risk of neurological dysfunction and death in patients > 65 years of age with unruptured intracranial aneurysms [20] . Increasing age is associated with higher neurological morbidity and mortality after pipeline embolization of intracranial aneurysms [21]. And in the study, age more than 65 years was an independent risk factor for coagulopathy and associated with higher mortality after aneurysm clipping.…”
Section: Discussionmentioning
confidence: 59%
“…23 The fusiform aneurysm was the only variable independently associated with postoperative stroke. 24 The PED is being used increasingly for off-label indications. For posterior circulation aneurysms, subgroup analysis from the IntrePED safety series showed neurologic morbidity and mortality comparable with reported rates after clipping or coiling.…”
Section: Conventional Braided Mesh Devicesmentioning
confidence: 99%